Study of contents of inguinal hernia in girls - Mankar, Kishor; Shinde, Nandkishor; Moinuddin, Mohammed; Ahmed, Ashfaq (International Surgery Journal, 2019)
Background: Inguinal hernia in females is relatively uncommon as compared to males. In female patients, the hernial sac contains one ovary in approximately 15–20% of cases, and some also contain a fallopian tube. This study was done to know the contents in inguinal hernia in girls. Methods: A prospective study on eight girls with inguinal hernia presenting between January 2016 to December 2018, presented with swelling in inguinal region. Physical examination in all girls was done followed by ultrasonogram to know the content of inguinal hernia. All patients underwent surgical exploration. Results: Among 8 girls with inguinal hernia, 2 (25%) girls had bilateral inguinal hernia, 4(50%) girls had right and 2 (25%) girls had left sided inguinal hernia. Ultrasonogram showed 2 girls with bilateral inguinal hernia had intestines as content on both sides. 3 girls had intestines, one (10%) girl had omentum and 2 (20%) girls had ovary as content of hernia sac. On surgical exploration one girl had omentum, one had ovary, two had intestine as hernial sac content. Two girls with irreducible hernia had omentum and ovary respectively as hernial content. In all girls after reduction of content, herniotomy was done. Conclusions: Surgical repair should be done at diagnosis in all girls presenting with inguinal hernia in view of high incidence of incarceration of ovary and tubes. Sac must be opened and its contents examined before it is tied off and excised.